Active and passive arm movements do not change affective evaluation - Áron Horváth; János Körmendi; Orsolya Drozdovszky; Vera Gál; Ferenc Köteles (PLoS ONE, 2025)
Previous research showed that the activation of the arm extensor muscles is associated with a more negative attitude. In contrast, arm flexor muscle activation is associated with a more positive one. However, most of the studies tested these effects with isometric activation of the muscles. The current study was conducted to test if these effects occur with actual passive and active forearm movement (i.e., isotonic muscle activation). 56 university students participated in this preregistered experiment. The study design consisted of two within-subject factors: (1) type of motion (i.e., the arm of the participants was moved actively or passively), and (2) movement direction (i.e., the arm moved toward the body, away from the body, or remained at the middle position. Participants rated their preferences toward Chinese-like ideographs. Data was analysed with repeated measures (2x3) ANCOVAs with state and trait affectivity (i.e., the experience of positive and negative emotional states at the moment and the general tendency to experience them) as covariates. No significant type of motion and direction main effects, and interaction were found. In conclusion, slight isotonic and passive movements of the forearm do not change the affective evaluation of stimuli. Systematic manipulation of the parameters, most importantly the muscle effort needed to move the forearm, could shed more light on the background of the results.